Short Interpregnancy Intervals: An Evidence-Based Guide for Clinicians. Issue 7 (July 2015) - Bigelow, Catherine A.; Bryant, Allison S.
Abstract : The interpregnancy interval (IPI) is the period of time between one birth outcome (live birth, miscarriage, stillbirth, or abortion) and conception of a subsequent pregnancy. Short IPI has been associated with obstetric, fetal, and maternal morbidity. While the literature has largely supported an ideal IPI of 18 to 23 months after live birth to minimize morbidity in a subsequent pregnancy, there are few references that can guide clinicians counseling patients about IPI after other pregnancy outcomes. In this article, we attempt to review, synthesize, and provide evidence-based IPI recommendations using the available literature. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner will be better able to discuss the definition of the interpregnancy interval, identify risk factors for short interpregnancy intervals, and interpret the available evidence for perinatal and maternal morbidity associated with short interpregnancy intervals.